2014
DOI: 10.3832/ifor1033-007
|View full text |Cite
|
Sign up to set email alerts
|

Local neighborhood competition following an extraordinary snow break event: implications for tree-individual growth

Abstract: Sustainable forest management practices and the increased interest of plantation forestry in species mixtures require an understanding of individual-tree growth in complex and diverse forests. Individual-tree growth has been found to be affected by factors such as species identity and size of the target tree as well as of neighboring trees, neighbor density and abiotic factors. However, most of these studies have been conducted in plantations or mixed forests with a very limited number of species. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…However, the little effect of neighborhood richness was consistent with previous studies carried out to analyze sapling growth in response to manipulated biodiversity in a nearby area (Lang et al 2012;Li et al 2014). In another study at the same site, Lang et al (2013) suggested that the local diversity effects on tree growth of four dominant species were reduced by the changes in complementary effects over time, local neighborhood species composition and snow break disturbance. These findings together indicate that neighborhood species composition and identity may play a more important role in tree growth than neighborhood species richness does (Lang et al 2012).…”
Section: Seasonal Similarity In Factors Influencing Tree Growth Ratessupporting
confidence: 88%
“…However, the little effect of neighborhood richness was consistent with previous studies carried out to analyze sapling growth in response to manipulated biodiversity in a nearby area (Lang et al 2012;Li et al 2014). In another study at the same site, Lang et al (2013) suggested that the local diversity effects on tree growth of four dominant species were reduced by the changes in complementary effects over time, local neighborhood species composition and snow break disturbance. These findings together indicate that neighborhood species composition and identity may play a more important role in tree growth than neighborhood species richness does (Lang et al 2012).…”
Section: Seasonal Similarity In Factors Influencing Tree Growth Ratessupporting
confidence: 88%
“…In addition, determinations of forest stand biomass have usually been considered to ensure sustainable management, and foresters have applied different methods to obtain such estimates [ 4 ]. In evenly-aged, simply structured monocultures, stand-based approaches are appropriate to explain and model tree growth [ 9 ]. Individual-tree growth models are fundamental components of forest growth and yield prediction frameworks [ 10 ].…”
Section: Introductionmentioning
confidence: 99%